Specifics of the Investment Attractiveness at Company Level - Plakhotnikova, L. O.; Bulakh Т. M. (Statistics of Ukraine, 2021)
Foreign investment is an essential factor in increasing the competitiveness of the national economy in our days. Investment is considered to be the main prerequisite for the social development, but the investment process faces many obstacles and problems not allowing to make it efficient and orderly. Intensification of investment processes is a priority objective of companies on the way to the sustainable development and enhanced competitive positions in the market environment. The investment attractiveness has critical significance in it, as its dynamism depends on the company’s ability to meet the terms of potential investors. In focus of the article are issues of attracting foreign capital as an important factor in accelerating technical progress and improving the company performance. The essence, types and significance of foreign investment in the context of globalization processes, relationships between the investment climate characteristics and the company competitiveness are determined. Factors of the investment capital reproduction increasing the capital cost at two levels, macro- and microeconomic, are discussed. An analysis of the performance and prospects of foreign investment in the Ukrainian business sector in the context of financial and economic globalization is made; the need for investment to ensure the company competitiveness in the conditions of economic crisis is justified. Approaches to the classification of factors determining investment climate and investment attractiveness were improved, which are defined at the macroeconomic and microeconomic level and involve their relationship and interaction. An analysis of interactions between transformation processes in the Ukrainian economy and investment activities revealed a correlation of the investment climate and the investment level with the company competitiveness on the market.